SISTEM INFORMASI PERPUSTAKAAN SDN BANYUAGUNG 1 SURAKARTA - , ALIF FAJAR RAHMAN S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Banyuagung 1st Elementary School has a library which good facilities from Surakarta Goverment. Everyday normally 20 until 40 the visitiors came to this library. This library still applied manual transaction. Tihs transaction like a borrow, return a book can be support to lost many archives and get trouble for many reports. Because of that, neet to information system for help good management at library. A good information system can help libraryâs management. This information system was made by Laravel framework, MySQL database and process planning use DAD. This system offers a simple data processing, transaction and make an automatic report. So, the official donât need to count many transaction data with manual system. The result, this development system can use for electronics transaction at library. The other benefit, this system can produce the soft file report too.